Mendorong Perkembangan Sosial Emosional Melalui Proyek Pembelajaran Berbasis Layanan Inklusif untuk Siswa IECE - Asih, Bimbi Lastri Prima; Syaodih, Ernawulan; Gustiana, Asep Deni; Zakir, Nordiana (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Aspects of social-emotional development are critical to young children’s overall development, in early childhood inclusive classrooms where children have a wide variety of needs. In Indonesia, a number inclusive education programs continue to grapple with the development of empathy, cooperation and emotional regulation, demonstrating that evidence-based strategies for young children to develop these abilities is an urgent priority. This investigation focused on the effect of service-learning experiences for children in inclusive early childhood programs. Twelve 5- to 6-year-old students participated from an inclusive classroom, using a mixed-method design. The collection of quantitative data was provided from PAPI testing, while the qualitative part consisted of classroom observations around peer interaction and affect regulation as well as semi-structured teacher interviews about engagement and feasibility. Students, overall, demonstrated a 32% average increase in social-emotional competence with the largest increase in empathy (35%), cooperation (30%) and emotional regulation (28%). Teachers noted better participation and cooperation between students as well. These results suggest that service-learning is an effective intervention for promoting social-emotional competence in inclusive preschool classrooms. The research contributes with practical applications for Indonesian educators and policy makers to implement service-learning in inclusive education that supports both social-emotional development as well as equitable learning beginning in the early years of education.